Impact of social factors responsible for Juvenile delinquency - A literature review - R Abhishek; J Balamurugan (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Juvenile delinquency appears to be the most widespread social issue in comparison to other social issues. Social factors and conditions have a significant impact on the prevalence of delinquency. Individuals who engage in criminal behavior before reaching the age of 18 are commonly referred to as juvenile offenders. The aim of this study is to comprehensively elucidate the research and work carried out on juvenile offenders, with a specific focus on the critical role played by social factors in all facets of juvenile delinquency. Additionally, this research seeks to investigate the social roots and influences that contribute to the criminal behavior of young offenders. MATERIALS AND METHODS: This article uses a literature review methodology to analyze research on social factors influencing juvenile delinquency. It synthesizes and evaluates prior findings to understand the complex interplay between social factors and young individuals' involvement in delinquent behaviors. The study analyzed 80 articles from reputable online databases, focusing on juvenile delinquency, offenders, crime, and social factors. Out of the 80 articles, 53 were cited, meeting inclusion criteria, including publication within 2000-2023, rigorous peer-review, and reputable database indexing. RESULTS: As per the findings of the research, it has been observed that children who grow up in households that exhibit affection, hospitality, and encouragement are comparatively less susceptible to the manifestation of societal maladies. Children who have experienced parental abandonment are at heightened risk of developing delinquent behaviors. CONCLUSION: The presence of negative family dynamics and associations with delinquent peers are widely recognized as significant contributors to the development of drug abuse behavior. It is imperative for policymakers and preventive initiatives to have a comprehensive understanding of this complex relationship. Therefore, this literature review presented a distinct overview of the influence of social factors on juvenile offenders in India.